Instructional Technology Classroom Integration and Math Scores of the Fifth Grade Students - Cyntha B. Pareja; Florante P. Ibarra; Amirul Mukminin; Lenny Marzulina; Kasinyo Harto; Herri Mulyono (Qubahan Academic Journal)
This study examined the instructional technology integration and Mathematics scores of 5th grade students in PARCC state assessment in school district of Maryland, USA. Constructed in the theoretical framework of Unified Theory Of Acceptance And Use Of Technology (UTAUT) by Venkatesh, Morris, Davis and Davis (2003), key variables that significantly contributes to outputs and the conceptual framework had been designed in the context of socio-demographic characteristics, instructional technology utilization, content delivery for mastery, and behavioral intentions to assess students mathematics performance through the use of instructional technology. Using descriptive and correlational designs, respondents were 91 students and 8 teachers participated in the study.  Results revealed that instructional technology utilization played significant role in the teaching and learning process.  The amount of time in using technology along with the socio-demographic characteristics such as area of specialization and educational attainment of parents were found to be positive predictors to students’ mathematics achievement.  Further in depth study on what procedure that contributes to student learning in mathematics whether learning the software process of computation versus manual calculation had been recommended.